Determinan Struktur Modal pada Perusahaan Sub Sektor Makanan dan Minuman di BEI 2020-2024 - Pingkan Mulyani; Bara Zaretta; Agus Prayitno; Amalia Nur Chasanah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the influence of company characteristics on capital structure, as proxied by short-term leverage, long-term leverage, and total leverage. The independent variables used include company size, profitability as proxied by ROA, tangible assets (tangibility), company growth (growth), and company risk (risk). This study uses panel data with 150 company observations during the study period and is analyzed using a panel data regression method with the Fixed Effect Model (FEM) approach as the best model. The results show that company size has a negative and significant effect on all capital structure proxies, namely short-term leverage, long-term leverage, and total leverage. Tangible assets have a significant negative effect on short-term leverage and total leverage, but have no significant effect on long-term leverage. Company risk has a significant positive effect on short-term leverage and total leverage, but has no significant effect on long-term leverage. Meanwhile, profitability and company growth do not show a significant effect on all capital structure proxies. The adjusted R-squared value indicates that the model has a fairly good ability to explain variations in company capital structure. These findings indicate that a company's capital structure decisions are more influenced by company size, risk, and asset characteristics than by profitability and company growth factors.